The Suitable COI Marker for Lobster of Genus Panulirus: COI Markers for Panulirus Lobster - Farajallah, Achmad; Tirtaningsih Handayani, Bintang Kusuma; Wardiatno, Yusli (Biological Sciences - PJSIR, 2019)
This study was conducted to analyze the COI (cytchrome oxidase subunit-1) sequences of members of the genus Panulirus, and determine the best region to use for species identification through DNA barcoding. Six samples were collected randomly from five sites in Indonesia. The three lobster species collected were P. femoristriga (Padang), P. homarus (Malang), and P. versicolor. A total of 1,516 sequences were analyzed using the software MEGA 6 for covering alignment, nucleotide variation, mutation rates, and genetic distance. Samples classified in the upper region (UR) consisted of 25 Panulirus species and 17 undetermined species, while samples classified in the lower region (LR) consisted of 11 Panulirus species and 2 undetermined species.